Preparation and Performance Characterization of High‐Quality HNIW. Issue 2 (22nd December 2021) - Xu, Wenzheng; Yan, Tianlun; Xu, Yang; Deng, Jie; Li, Hao; Li, Yuexin; Guo, Fengwei; Wang, Jingyu; Gao, Feng
Abstract: In this study, high‐quality HNIW was prepared by solvent‐antisolvent recrystallization method and mechanical ball‐milling method. The particle morphology, particle size, crystal form, and thermal stability of HNIW samples were characterized by SEM, DSC, and XRD. The purity of HNIW samples was characterized by the HPLC. The HGZ‐1 impact sensitivity meter and WM‐1 friction sensitivity meter were used to evaluate the impact sensitivity and friction sensitivity respectively. The detonation voltage of the samples was tested by the EFI system. Compared with the micron‐level HNIW obtained by four times of recrystallizations, the particle size grading mechanical ball milling method of grinding balls minimizes the particle size of the HNIW. The prepared nano‐level HNIW has an average particle size of about 200 nm and has the advantages of narrow distribution, low mechanical sensitivity, and good detonation performance. Therefore, the solvent‐antisolvent recrystallization method and mechanical ball‐milling method can be used to obtain nano‐HNIW with a narrow particle size distribution, high purity, and good performance. Abstract :